Common Factors and Nutrients Affecting Intestinal Villus Height - Ali Abdul Ameer Ghadban; Israa Badi Khalaf; Ali M. Attai (Universitas Muhammadiyah Sidoarjo, 2026)
General Background: The avian digestive system exhibits structural adaptations that enable rapid digestion and nutrient absorption from diverse food sources. Specific Background: The small intestine, consisting of duodenum, jejunum, and ileum, plays a central role in digestion, with morphological variations observed among bird species. Knowledge Gap: However, limited comparative data exist regarding how intestinal morphology, length, and weight differ among bird species with varying dietary patterns. Aims: This study aims to determine morphological characteristics and morphometric variations of the small intestine in seven bird species with different feeding types. Results: The findings reveal significant differences (p≤0.05) in intestinal length, weight, and structural configuration among species, with the mallard exhibiting the longest intestine and zebra finch the shortest, while variations in jejunum shape were identified as U-shaped, cone-shaped, or short and wide depending on species. The ratio of intestinal length and weight relative to body size also differed markedly. Novelty: This study provides a comparative morphological dataset linking intestinal structure with dietary variation across multiple avian species. Implications: These results contribute to understanding digestive adaptation in birds and provide anatomical references for veterinary and comparative physiology studies. Highlights: • Significant Variation in Intestinal Measurements Observed Across Seven Avian Species• Jejunum Configuration Differs Into Three Distinct Structural Patterns Among Species• Dietary Type Corresponds With Variation in Intestinal Proportions and Structure Keywords: Avian Anatomy, Small Intestine, Morphology, Digestive System, Bird Nutrition.